Use of single-inhaler triple therapy in the management of obstructive airway disease: Indian medical experts' review. Issue 1 (28th March 2022) - Dhar, Raja; Talwar, Deepak; Salvi, Sundeep; Muralimohan, B.V.; Panchal, Sagar; Patil, Saiprasad; Bhagat, Sagar; Khatri, Nishtha; Barkate, Hanmant
Obstructive airway disease (OAD), which includes COPD and asthma, is the leading cause of morbidity and mortality in India. Long-acting bronchodilators (long-acting β2 agonists (LABAs) and/or long-acting muscarinic antagonists (LAMAs)) and inhaled corticosteroids (ICS) have a vital role in the management of patients with OAD. While symptom burden and exacerbations are common amongst treated patients, poor adherence to inhaler therapy is a frequent challenge. Better treatment options that optimise symptom control, improve quality of life, reduce exacerbation risk and improve adherence are desired. Triple therapy (ICS/LABA/LAMA) is recommended in the Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2021 guidelines for symptomatic COPD patients on ICS/LABA or LABA/LAMA, and who are at increased risk for frequent or severe exacerbations. Similarly, add-on LAMA is recommended in uncontrolled asthma patients on medium- to high-dose ICS/LABA by the Global Initiative for Asthma (GINA) 2021 guideline. In the real world, high-risk and overlapping phenotypes exist, which necessitate early initiation of triple therapy. We aim to provide an expert review on the use of single-inhaler triple therapy (SITT) for OAD management in global and Indian settings, knowledge from which can be extrapolated for appropriate treatment of Indian patients. The OAD population in India may benefit from early optimisation to SITT characterised by a high burden of exacerbating OAD, nonsmoker COPD and asthma–COPD overlap. SITT has been shown to reduce exacerbations and improve symptom control and QoL in OAD. Additionally, evidence suggests improved adherence with SITT. Further real-world studies are needed to substantiate the benefits of SITT in OAD, especially asthma. https://bit.ly/3IfwnUZ